2003
DOI: 10.1074/jbc.m212911200
|View full text |Cite
|
Sign up to set email alerts
|

Trapping HIV-1 Reverse Transcriptase Before and After Translocation on DNA

Abstract: A disulfide cross-linking strategy was used to covalently trap as a stable complex (complex N) a shortlived, kinetic intermediate in DNA polymerization. This intermediate corresponds to the product of polymerization prior to translocation. We also prepared the trapped complex that corresponds to the product of polymerization after translocation (complex P). The crosslinking method that we used is a variation of a technique developed by the Verdine and Harrison laboratories. It involves disulfide interchange be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
85
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 26 publications
4
85
0
Order By: Relevance
“…Template and primer were first annealed at 95°C for 5 min, cooled at room temperature for 20 min, and stored at −20°C. The 15 μM annealed template/primer (T/P) substrates were incubated with 7 μM cross-linkable HIV RT in 25 mM Tris, pH 8.0, 100 mM NaCl, 10 mM MgCl 2 , and 0.1 mM 2′,3′-dideoxyguanosine-5′-triphosphate (ddG-TP) (GE Health Life Science) to obtain the RT/DNA ddG-MP P complex; 70 μM EFdA-TP and 0.1 mM deoxythymidine monophosphate (dT-MP) for the RT/DNA EFdA-MP P •dT-MP N binary complex; or 70 μM EFdA-TP for the RT/DNA EFdA-MP P •EFdA-MP N and RT/DNA EFdA-MP P •EFdA-MP *N complexes at 31°C for 18 h. Cross-linked RT-dsDNA complex was purified using a Ni-Heparin tandem column strategy (20). Cross-linking efficiency was judged by an increase in the molecular weight of the p66 subunit in nonreducing SDS/PAGE.…”
Section: Methodsmentioning
confidence: 99%
“…Template and primer were first annealed at 95°C for 5 min, cooled at room temperature for 20 min, and stored at −20°C. The 15 μM annealed template/primer (T/P) substrates were incubated with 7 μM cross-linkable HIV RT in 25 mM Tris, pH 8.0, 100 mM NaCl, 10 mM MgCl 2 , and 0.1 mM 2′,3′-dideoxyguanosine-5′-triphosphate (ddG-TP) (GE Health Life Science) to obtain the RT/DNA ddG-MP P complex; 70 μM EFdA-TP and 0.1 mM deoxythymidine monophosphate (dT-MP) for the RT/DNA EFdA-MP P •dT-MP N binary complex; or 70 μM EFdA-TP for the RT/DNA EFdA-MP P •EFdA-MP N and RT/DNA EFdA-MP P •EFdA-MP *N complexes at 31°C for 18 h. Cross-linked RT-dsDNA complex was purified using a Ni-Heparin tandem column strategy (20). Cross-linking efficiency was judged by an increase in the molecular weight of the p66 subunit in nonreducing SDS/PAGE.…”
Section: Methodsmentioning
confidence: 99%
“…The other major resistance mechanism involves ATP-mediated phosphorolytic excision of the incorporated chain-terminating NRTI from the 3Ј-end of the primer (27,28). We and others have previously shown that for excision to occur, the 3Ј-end of the primer must be positioned at the pre-translocation or N-site of RT (19,29,30). As we have already shown, the 3Ј-EFdA-MP-terminated primer strand binds predominantly in a pre-translocation mode.…”
Section: Incorporation Of Efda-tp Into Dna (T/p Efda-mp ) Decreases Tmentioning
confidence: 99%
“…The latter configuration is referred to as the post-translocational state. Cross-linking experiments revealed that pyrophosphorolysis or the ATP-dependent excision can only occur in the former pre-translocational state (26,27). To account for the non-competitive mode of inhibition it has been suggested that PFA may likewise bind to the pre-translocated complex (8).…”
mentioning
confidence: 99%